Axial Flux Permanent Magnet Brushless Machines - Gieras, Jacek F.; Wang, Rong-Jie; Kamper, Maarten J. (Springer Netherlands : Imprint: Springer, 2008)
Axial Flux Permanent Magnet (AFPM) brushless machines are modern electrical machines with a lot of advantages over their conventional counterparts. They are being increasingly used in consumer electronics, public life, instrumentation and automation system, clinical engineering, industrial electromechanical drives, automobile manufacturing industry, electric and hybrid electric vehicles, marine vessels and toys. They are also used in more electric aircrafts and many other applications on larger scale. New applications have also emerged in distributed generation systems (wind turbine generators, high-speed micro turbine generators), miniature power supplies, flywheel energy storages, aircraft and rotorcraft actuators, missile fin actuators, naval integrated motor-propellers (rim driven thrusters). The role of axial flux PM brushless machines is increasing especially in applications where integration of motors with other mechanical parts is imperative. This book deals with the analysis, construction, design, control and applications of AFPM machines. The authors present their own research results, as well as significant research contributions made by others. Growing interest in new topologies of permanent magnet (PM) brushless machines has prompted the authors to update the first edition of Axial Flux Permanent Magnet Brushless Machines. In this second edition new sections (non-overlap concentrated coil windings, rotor dynamics, miniature axial flux PM motors, in-wheel motors), new examples of applications and more numerical examples have been added. This monograph will be of interest to electrical engineers and other engineers involved in the design and application of AFPM brushless machine drives. It will be an important resource for researchers and graduate students in the field of electrical machine and drives.